A comparative study on Monte Carlo simulations of electron emission from liquid water. Issue 2 (25th December 2019) - Mehnaz; Yang, L.H.; Zou, Y.B.; Da, B.; Mao, S.F.; Li, H.M.; Zhao, Y.F.; Ding, Z.J.
Abstract : Purpose: Liquid water being the major constituent of the human body, is of fundamental importance in radiobiological research. Hence, the knowledge of electron‐water interaction physics and particularly the secondary electron yield is essential. However, to date, only very little is known experimentally on the low energy electron interaction with liquid water because of certain practical limitations. The purpose of this study was to gain some useful information about electron emission from water using a Monte Carlo (MC) simulation technique that can numerically model electron transport trajectories in water. Methods: In this study, we have performed MC simulations of electron emission from liquid water in the primary energy range of 50 eV–30 keV by using two different codes, i.e., a classical trajectory MC (CMC) code developed in our laboratory and the Geant4‐DNA (G4DNA) code. The calculated secondary electron yield and electron backscattering coefficient are compared with experimental results wherever applicable to verify the validity of physical models for the electron‐water interaction. Results: The secondary electron yield vs. primary energy curves calculated using the two codes present the same generic curve shape as that of metals but in rather different absolute values. G4DNA underestimates the secondary electron yield due to the application of one step thermalization model by setting a cutoff energy at 10 eV so that the low energy losses due to phonon excitations are omitted. Our CMC code, using a full energy loss spectrum to model electron inelastic scattering, allows the simulation of individual phonon scattering events for very low energy losses down to 10 meV, which then enables the calculated secondary electron yields much closer to the experimental data and also gives quite reasonable energy distribution curve of secondary electrons. Conclusions: It is concluded that full dielectric function data at low energy loss values below 10 eV are recommended for modeling of low energy electrons in liquid water.